Chronicling the experiences and beliefs of mathematics student teachers and their educators on their practices - Olawale, Babawande Emmanuel; Hendricks, Winston (Universitas Muhammadiyah Surakarta, 2022)
Understanding the experiences of those undergoing teacher education and their educators is central to pedagogical practices. While some studies have found that experiences and beliefs influence instructional decisions, others revealed that practice influences beliefs. Although the complexity of the relationship between conceptions and practice defies the simplicity of cause and effect, much of the contrast in the teachers’ instructional emphasis may be explained by differences in their prevailing views of mathematics. As such, the present study examined the experiences and beliefs of mathematics student teachers and their teacher educators on their practices. The study employed a qualitative research approach and a case study design; data was gathered using document reviews, observations, and interviews. For this study, seventy-five mathematics student teachers and six mathematics teacher educators were purposively sampled from three traditional South African universities. Data collected for this study were analyzed thematically. Research findings revealed that teacher education program positively influences mathematics student teachers’ beliefs of their practices. On the contrary, mathematics teacher educators’ educational background and teaching experiences contribute little to no to their teaching, making their practices authoritative. The study concludes that the emotional, relational, and moral viability of pedagogical methods is dependent on the experiences of those undergoing mathematics teacher preparation programs and their educators. As a result, development programs for mathematics teacher educators are critical, with the goal of upskilling them in how to set up and manage more participatory classrooms